X-ray tomography applied to the void/defect measurement of hybrid CFRC/SiC composites - De Souza, Maria Aparecida Miranda [UNESP]; Pardini, Luiz Claudio; Botelho, Edson Cocchieri [UNESP]; Costa, Michelle Leali [UNESP] (IOP Publishing, 2019)
Carbon fiber reinforced carbon composites (CFRC) and carbon fiber reinforced silicon carbide composites (CFRC/SiC) are materials of wide interest in the aerospace industry due mainly to their outstanding thermo-mechanical properties at high temperature. The control of the process of obtaining these composites, carried out non-destructive processes, such as x-ray tomography, are of great interest to the industry, since they are able to present not only information concerning density and porosity, but also 3D vision with identification of closed and open pores, as well as a precise location of these defects in the sample. In this study a CFRC/SiC hybrid matrix composite obtained by employing carbon-silicon reaction by direct impregnation of silicon powder and phenolic resin, followed by heat treatment at 1600 °Cunder inert atmosphere is monitored step by step, in its preparation stages, using x-ray computed tomography techniques compared with optical microscopy techniques to detect voids in its microstructure. The three methods presented were satisfactory for structural analysis of the steps of obtaining the CFRC/SiC composite, considering the resolution and sample preparation restrictions applied to each of them, under the working conditions described in this study.
Keywords: Cfrc/sic composites; Optical microscopy; Voids; X-ray tomography